Beyond Words: The Analysis of Gottlieb’s Subtitling Theory in 'Leap Year's' movie. - Andi Asti Rianasari Tumba; Prasetyo Wibowo, Agung (International Journal of English and Applied Linguistics (IJEAL), 2024)
Audiovisual translation refers to translating audiovisual media's spoken and written elements, one example of which is through films. This article aimed to analyze the subtitles of the movie Leap Year using an audiovisual translation. It focused on subtitling strategies using Gottlieb’s theory, which consists of 10 strategies: Expansion, Paraphrase, Transfer, Imitation, Displacement, Condensation, Transcription, Decimation, Deletion, and Resignation. The researcher used qualitative methods to collect the data and watched the film Leap Year. The results showed that were only four strategies out of ten in analyze The Leap Year Movie (2010), they were: 3 of Expansion, 4 Transfer, 1 of Deletion, 2 of Imitation.